2007
DOI: 10.1175/jtech1978.1
|View full text |Cite
|
Sign up to set email alerts
|

Determining Weather Radar Antenna Pointing Using Signals Detected from the Sun at Low Antenna Elevations

Abstract: A method to determine the elevation and azimuth biases of the radar antenna using solar signals observed by a scanning radar is presented. Data recorded at low elevation angles where the atmospheric refraction has a significant effect on the propagation of the radio wave are used, and a method to take the effect of the refraction into account in the analysis is presented. A set of equations is given by which the refraction of the radio waves as a function of the relative humidity can easily be calculated. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 1 publication
1
95
0
Order By: Relevance
“…The wavelength is set at 5.0 cm (note that the k-Model and thus our refraction equations are valid for all radiowave frequencies), and the relative humidity is set at 20, 60, or 100%. For the surface temperature and pressure prescribed by the Standard Atmosphere, the reference surface refractivity of N 0 = 313 corresponds to a relative humidity of just below 60%, which is also the optimum value according to Huuskonen and Holleman [2007].…”
Section: Comparison With Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wavelength is set at 5.0 cm (note that the k-Model and thus our refraction equations are valid for all radiowave frequencies), and the relative humidity is set at 20, 60, or 100%. For the surface temperature and pressure prescribed by the Standard Atmosphere, the reference surface refractivity of N 0 = 313 corresponds to a relative humidity of just below 60%, which is also the optimum value according to Huuskonen and Holleman [2007].…”
Section: Comparison With Calculationsmentioning
confidence: 99%
“…For instance, radio signals from the Sun are used for monitoring of the antenna alignment and the receiving chain of weather radars [Huuskonen and Holleman, 2007;Holleman et al, 2010aHolleman et al, , 2010b. As weather radars scan close to the horizon, the intercepted radio signals originate from a rising or setting Sun and thus atmospheric refraction is an issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration of antenna pointing has been discussed by Darlington et al (2003) and Huuskonen and Holleman (2007). Darlington et al (2003) proposed a method to monitor the antenna pointing accuracy at low elevation angles using the Sun as reference.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the average pointing error for the Chenies radar in the United Kingdom was about 1.0°with a standard deviation of 0.1°over 1-month period. Huuskonen and Holleman (2007) improved Darlington et al (2003) algorithm to account for significant effects in atmospheric refraction. However, sometimes it is not convenient to use the Sun for continuous checking of the azimuthal angle and therefore there is a need for a new methodology to regularly monitor the azimuthal radar antenna beam positions in real-time.…”
Section: Introductionmentioning
confidence: 99%